Implementasi Algoritme Grain 128 Pada Proses Pengiriman Data Menggunakan Raspberry Pi 3 - Moh. Afif Ma'ruf; Ari Kusyanti; Adhitya Bhawiyuga (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Internet of Things (IoT) is one of positive effects in development of new technology in modern communication networks. Data leakage is negative impact of security and confidentiality issues. This issues must be considered, so that unauthorized parties cannot access or modify contents of the data. From these problems a cryptographic technique is needed to secure data. One algorithm that can be used is Grain 128. Grain 128 is a stream cipher algorithm that has a high speed performance with very low memory and power. The client and server communication media used TCP/IP protocol. Raspberry Pi 3 used as a client or gateway that sends files, then encrypts files when sent and laptop as server that will decrypt when files are received. There are 5 experiments to ensure system can run properly. In this study, experiments carried out include functional testing, test vector validation, encryption and decryption, security and performance testing. In functional testing, result showed that all functionality is valid. In keystream test vector validation, keystream first generated and compared with test vector in official paper released, from this experiment results show keystream generated is valid. In encryption and decryption test, system can run and received file, contents of the file cannot be read while sending. In security testing the data sent cannot be sniffed using Wireshark. In performance testing, 5 different file formats with the extension DOCX, PPT, XLSX, TXT, and PDF was tested. The experiment carried out 30 times and average delivery result was 47.1 seconds. Files with PDF format have the fastest execution time average of 43.4 seconds.